2018
DOI: 10.1016/j.ejpn.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neurodevelopmental outcome after perinatal arterial ischemic stroke and periventricular venous infarction

Abstract: In this national cohort, poor long-term neurodevelopmental outcome after perinatal ischemic stroke was seen irrespective of the vascular type or time of diagnosis of stroke. However, the spectrum of neurological deficits is different after perinatal AIS and PVI, with combined deficits more common among children following AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 47 publications
3
33
0
3
Order By: Relevance
“…In children with PVI, a study of intellectual development in 62 children found 76% to have typical development or mild intellectual disability, 23% with moderate intellectual disability, and one child with a severe intellectual disability 122 . Another study of 18 children with PVI found lower average IQ scores but no cases with extremely low cognitive ability 123 . Application of formal neuropsychological evaluations in a school‐aged cohort of children with fetal GMH‐IVH would be required to better characterize these outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children with PVI, a study of intellectual development in 62 children found 76% to have typical development or mild intellectual disability, 23% with moderate intellectual disability, and one child with a severe intellectual disability 122 . Another study of 18 children with PVI found lower average IQ scores but no cases with extremely low cognitive ability 123 . Application of formal neuropsychological evaluations in a school‐aged cohort of children with fetal GMH‐IVH would be required to better characterize these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…122 Another study of 18 children with PVI found lower average IQ scores but no cases with extremely low cognitive ability. 123 Application of formal neuropsychological evaluations in a school-aged cohort of children with fetal GMH-IVH would be required to better characterize these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for non-verbal functions in patients with leftsided lesions, language reorganization has been proposed as a modifying factor (6,7,14). This has been explained in the context of the "crowding hypothesis" (15)(16)(17), suggesting that cognitive processes originally located in the right hemisphere such as nonverbal intelligence show deficits when language functions shift to the right hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…It affects mostly term-born newborns, and presents with diverse signs and symptoms ( 2 ). Outcome is quite variable, with many children achieving normal levels of function ( 3 , 4 ), while others experience difficulties, such as impairment in different domains of cognitive functions ( 5 7 ) as well as in motor skills ( 8 10 ). Potentially modifying factors explaining the variability in cognitive outcome are lesion size, the severity of hand motor impairment ( 6 ), and the side of the lesion ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation